Effect of Foliar Application of Micronutrients on Yield and Quality of Pomegranate - Yadav, Dinesh K.; Meena, Yogendra K.; Deewan, Parvati; Gupta, Deepak (International Journal of Bio-resource and Stress Management, 2022)
An experiment was conducted to evaluate the response to the foliar application of micro nutrient viz. iron, zinc and boron in single or in different combination on pomegranate in randomized block design with nine treatments and four replications during the mrig bhahar season kharif (June–July flowering time, 2016, 2017 and 2018) at Agriculture Research sub–Station Gonera Kotputli, Jaipur. Rajasthan, India. A perusal pooled data indicated that the different treatments of micronutrients application in pomegranate had significant effect on growth, yield and quality of pomegranate. The micronutrients spraying resulted in higher yield due to increased growth, better flowering and higher fruit set. The early initiation of flowering (44.8 Days), highest fruit set (52.66%), highest number of fruits plant-1 (87.37 fruit plant-1), yield of fruit (20.37 kg plant-1), B:C ratio (2.99), less fruit cracking (3.82%), high TSS (14.83%), low acidity (0.91 %), high TSS/ acid ratio (16.39) and low fruit drop (0.56 %) were observed under spray of ferrous sulphate @ 0.5%+zinc sulphate @ 0.5%+borax @ 0.4% (T8). Whereas control condition T1 late initiation of flowering (49 days), lowest fruit set (42.61%), lowest number of fruits plant-1 (69.75 fruit plant-1), yield of fruit (14.33 kg plant-1), B:C ratio (2.13), high fruit cracking (15.36 %), low TSS (13.45 %), higher acidity (1.48 %), low TSS/ acid ratio (9.09) and higher fruit drop (2.04 %) was recorded.